2004
DOI: 10.1038/labinvest.3700043
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized β-catenin promotes hepatocyte proliferation and inhibits TNFα-induced apoptosis

Abstract: The human hepatocellular carcinoma (HCC) is one of the most common malignant tumors worldwide. The mechanisms of liver cell oncogenic transformation are still unknown. The b-catenin mutations are identified in up to 30% of HCC and 80% of hepatoblastoma, suggesting a potential role of b-catenin in the pathogenesis of liver cancers. To define the biological role of the stabilized b-catenin in liver cell growth and transformation, we examined the effect of mutant b-catenin on an immortalized murine hepatocyte cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…In prehypertrophic and hypertrophic chondrocytes committed to maturation, ␤-catenin induces terminal differentiation (6,34). The current findings similarly suggest that, in proliferating and immature chondrocytes, ␤-catenin acts downstream of TGF-␤ and functions to stimulate chondrocyte proliferation, consistent with an effect on proliferation in other cell types (37)(38)(39). Thus, a possible explanation of the role of TGF-␤ signaling in modulating Wnt canonical signaling during cell growth versus differentiation is that SMAD3 enhances ␤-catenin signaling during cell proliferation but inhibits signaling in more differentiated chondrocytes progressing toward terminal maturation.…”
Section: Discussionsupporting
confidence: 75%
“…In prehypertrophic and hypertrophic chondrocytes committed to maturation, ␤-catenin induces terminal differentiation (6,34). The current findings similarly suggest that, in proliferating and immature chondrocytes, ␤-catenin acts downstream of TGF-␤ and functions to stimulate chondrocyte proliferation, consistent with an effect on proliferation in other cell types (37)(38)(39). Thus, a possible explanation of the role of TGF-␤ signaling in modulating Wnt canonical signaling during cell growth versus differentiation is that SMAD3 enhances ␤-catenin signaling during cell proliferation but inhibits signaling in more differentiated chondrocytes progressing toward terminal maturation.…”
Section: Discussionsupporting
confidence: 75%
“…35,36 Knockdown of b-catenin gene expression using RNA interference results in cell growth arrest and detachment, whereas stabilization of b-catenin suppresses cell apoptosis. [37][38][39][40][41][42][43] In this study, we have shown that CVB3 infection decreases protein expression of b-catenin via a GSK3b-dependent mechanism, and overexpression of b-catenin inhibits CVB3-induced apoptosis and CPE. These findings suggest b-catenin is a key downstream effector of GSK3b in the regulation of apoptosis and cell morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentrations were determined from the supernatants using the BioRad Lowry Protein Assay and protein spectrophotometer (750 nm) as previously reported. 16 …”
Section: Materials and Methods Tissue Samplesmentioning
confidence: 99%
“…19 Procedures of RNA and DNA extraction from liver cancer cell lines, PCR, and RT-PCR analysis were previously published. 16 The primers for CPS1 RT-PCR analysis were: 5 0 ATGCGGCCGCAGCCACA AATCATCTTCAAAA; 5 0 CGTCTAGATGAGAAAGTTGTGA ATCAGTTCC, and primers for PCR analysis were 5 0 -CAA CTCAGCATGGCATTGAC; 5 0 -ACAGCTGTCCTCCGAATCAC.…”
Section: Mass Spectrometrymentioning
confidence: 99%